Gender, Race, and Ethnicity Representation Among Gastroenterologists: A Review of Recent Trends. (17th October 2022) - Rahal, Harman; Girotra, Mohit; May, Folasade P.; Tabibian, James H.
Abstract : Diversity in medicine and the gastroenterology (GI) subspecialty is a topic warranting attention, especially in light of a number of recent incidents highlighting the persistence of racial, ethnic, and gender injustice in our nation. Insight into this topic is important insofar as the multitude of racial, ethnic, and gender backgrounds comprising the national patient population should be reflected, to the degree possible, by the providers serving it. Inclusion becomes particularly imperative because the quality of health care and health research and bridging disparities may be closely linked to adequate representation among healthcare providers. Despite the urgency of this topic, there is a paucity of data examining trends in gender and racial/ethnic diversity among medical professionals within the field of GI. In this narrative review, we examine how ethnoracial and gender representation has changed over time at critical points along the educational, training, and career pathways in GI.